Strategi Pemasaran Dalam Meningkatkan Omset Penjualan Pada Rumah Makan Padang Uni Ross Kendari - Wulandari, Putri; Nasrul, Nasrul; Nur, Muh. (International Journal Labs, 2025)
Uni Ross Padang Restaurant Kendari is a culinary business. The sales of the food menu offered at the Uni Ross Padang Restaurant are very diverse, but the turnover received from month to month is still unstable. Seeing these problems, a development strategy is needed at the Uni Ross Padang Restaurant in Kendari to overcome these turnover problems. This study aims to determine and analyse marketing strategies to increase the amount of turnover at the Uni Ross Kendari Restaurant. The method used in this research is descriptive quantitative with the SWOT (Strength-Weakness Opportunity-Threats Analysis) and QSPM (Quantitative Strategic Planning Matrix) method approaches. Data processing is carried out using an internal factor evaluation (IFE) matrix and an external factor evaluation (EFE) matrix. Based on the results of the calculation, the IFE score obtained is 2.33 and the EFE score is 2.03. Furthermore, the results of SWOT and QSPM analysis obtained a priority strategy that must be carried out is to optimise strategic business locations to attract people's purchasing power with a TAS value of 6.44. Thus, the main focus that needs to be developed by Rumah Makan Padang Uni Ross Kendari is to maximise the potential of business locations, businesses can improve operational efficiency and achieve more stable growth.